Atuação do mercado financeiro como fonte de financiamento para o desenvolvimento sustentável: o papel dos Green Bonds em meio à financeirização - Henrique Bracarense Fagioli (2022)
Achieving sustainable development goals is an urgent necessity, not only due to the inevitability of climate change but also because of the current levels of income inequality worldwide. Hence, the need for sources of finance is growing. However, access to capital is lacking as a consequence of the reconfiguration of the system in the post-Great Recession of 2008. Whereas liberalization led to the protagonism of financial capital markets to the detriment of banking finance, the intensification of volatility and the systemic dispersal of risk restricted the possibility of attaining financial resources, especially in the case of developing countries. Thus, there is space for innovations, the most promising ones being green bonds, characterized as operations of debt emission with high transparency, external review, and formal statement of the use of proceeds for sustainable goals. However, the financialization of the economy, a by product of the liberalization process in the last decades, requires a critical investigation, especially regarding the role green bonds perform in financing sustainable development. The objective of this study is to analyze whether green bonds are sustainability-aligned innovations or just an aspect of the financialization of nature. First, the study describes global and Brazilian green bond markets during 2014-2021, aiming to verify the convergences and divergences of those markets with the traditional bond markets. Secondly, assuming the existence of a green risk premium, or greenium, in the pricing of green bonds as evidence of establishing their financialized behavior, a methodology proper to the Brazilian case is developed to plot the yield curves of thirteen bonds. Results indicate that there is no significantly distinct behavior in premia for green bonds compared to traditional ones.